2007
DOI: 10.1038/sj.leu.2404928
|View full text |Cite
|
Sign up to set email alerts
|

Genetically identical twin transplantation for chronic lymphocytic leukemia

Abstract: We identified 19 persons with B-cell chronic lymphocytic leukemia (CLL) who received genetically identical twin blood cell or bone marrow transplants after high-dose conditioning. Ten are alive (eight disease-free) with a median follow-up of 89 months (range, 31-171 months); 5-year relapse rate was 50% (95% confidence interval (CI), 26-73%). Estimated 5-year survival and disease-free survival were 61% (95% CI, 37-82%) and 45% (95% CI, 23-68%). In two of four patients tested at 12 and 21 months by polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…30,31 To date, however, MBL has not been reported in any recipients following blood transfusion. Indeed, no MBL studies have been conducted in transfusion recipients.…”
mentioning
confidence: 99%
“…30,31 To date, however, MBL has not been reported in any recipients following blood transfusion. Indeed, no MBL studies have been conducted in transfusion recipients.…”
mentioning
confidence: 99%
“…Others have reached similar conclusions with less extensive analyses. 29,34,35 However, a more critical analysis of GvL in CLL requires considering detailed data from larger numbers of allograft recipients with and without GvHD, recipients of T-cell-depleted allograft and genetically identical twin transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such data are reported few in number. Pavletic et al 34,35 reported 19 subjects transplanted between 1980 and 2001 with bone marrow or blood cell transplants after high doses of pretransplant anti-leukemia drugs with or without radiation. Four of 13 subjects achieving complete remission relapsed with a 5-year cumulative relapse risk of 52% (95% confidence interval, 27-77%).…”
Section: Transplants From Genetically Identical Twinsmentioning
confidence: 99%
“…There is both the theoretical and actual concern for transfer of MBL and leukemia stem cells to recipients, especially in the setting of an immunodepressed recipient. Several occurrences of transfer of MBL donor clones to a CLL patient undergoing transplant resulting in a second CLL in the recipient have been documented (40)(41)(42). Three case studies of potential population-screened MBL donors and a detailed review of ethical issues can be found in Hardy et al (29).…”
Section: Clinicalmentioning
confidence: 99%